Hybrid methodology to analyse reliability and techno‐economic evaluation of microgrid configurations. Issue 21 (23rd October 2019) - Rana, Ankur Singh; Iqbal, Fahad; Siddiqui, Anwar Shahzad; Thomas, Mini Shaji
Abstract : Concerns related to environmental pollution, growing population, fossil fuel depletion, ever‐increasing load demands etc. lead power utilities to rely on renewable energy resources (RERs). The objective of the research is to evaluate the reliability of the microgrid by focussing on the economic and environmental benefits of RERs. Reliability assessment of power network plays an important role to achieve high demands of reliable power supply globally. Reliability assessment helps power utilities in reducing the frequency and the duration of power outages to their customers. In this work, the impact of a stochastic characteristic of photovoltaic system, wind turbine generator system, and battery storage on the overall reliability of the power system are analysed in both the scenarios, i.e. grid‐connected and isolated mode of operation of the microgrid. Various configurations of microgrid based on redundancy levels are considered for reliability evaluation, including common cause outages and miscoordination of protection devices. The effect of addition and removal of different distributed generation units on the overall reliability of the system is analysed using Markov approach. Also, techno‐economic analysis of different reliable configurations is performed to finalise the best possible reliable and economic configuration of the microgrid.